Comparison of Fourteen Reference Evapotranspiration Models With Lysimeter Measurements at a Site in the Humid Alpine Meadow, Northeastern Qinghai-Tibetan Plateau - Dai, Licong; Fu, Ruiyu; Zhao, Zhihui; Guo, Xiaowei; Du, Yangong; Hu, Zhongmin; Cao, Guangmin (Frontiers in Plant Science, 2022)
Evapotranspiration is a key component in the terrestrial water cycle, and accurate evapotranspiration estimates are critical for water irrigation management. Although many applicable evapotranspiration models have been developed, they are largely focused on low-altitude regions, with little attention given to alpine ecosystems. In this study, we evaluated the performance of fourteen reference evapotranspiration (ET0) models by comparison with large weight lysimeter measurements. Specifically, we used the Bowen ratio energy balance method (BREB), three combination models, seven radiation-based models, and three temperature-based models based on data from June 2017 to December 2018 in a humid alpine meadow in the northeastern Qinghai–Tibetan Plateau. The daily actual evapotranspiration (ETa) data were obtained using large weighing lysimeters located in an alpine Kobresia meadow. We found that the performance of the fourteen ET0 models, ranked on the basis of their root mean square error (RMSE), decreased in the following order: BREB > Priestley-Taylor (PT) > DeBruin-Keijman (DK) > 1963 Penman > FAO-24 Penman > FAO-56 Penman–Monteith > IRMAK1 > Makkink (1957) > Makkink (1967) > Makkink > IRMAK2 > Hargreaves (HAR) > Hargreaves1 (HAR1) > Hargreaves2 (HAR2). For the combination models, the FAO-24 Penman model yielded the highest correlation, followed by 1963 Penman and FAO-56 PM. For radiation-based models, PT and DK obtained the highest correlation, followed by Makkink (1967), Makkink (1957), IRMAK1, and IRMAK2. For temperature-based models, HAR, HAR1, and HAR2 obtained the same correlation. Overall, the BREB performed best, with RMSEs 0.98, followed by combination models (ranging from 1.19 to 1.27 mm d−1 and averaging 1.22 mm d−1), radiation-based models (ranging from 1.02 to 1.42 mm d−1 and averaging 1.27 mm d−1), and temperature-based models (ranging from 1.47 to 1.48 mmd−1 and averaging 1.47 mm d−1). Furthermore, all models tended to underestimate the measured ETa during periods of high evaporative demand (i.e., growing season) and overestimated measured ETa during low evaporative demand (i.e., non-growing season). Our results provide new insights into the accurate assessment of evapotranspiration in humid alpine meadows in the northeastern Qinghai–Tibetan Plateau.